2004
DOI: 10.1007/s00299-004-0756-4
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium rhizogenes -mediated DNA transfer to Aesculu s hippocastanum L. and the regeneration of transformed plants

Abstract: Hairy roots were induced from androgenic embryos of horse chestnut (Aesculus hippocastanum L.) by infection with Agrobacterium rhizogenes strain A4GUS. Single roots were selected according to their morphology in the absence of antibiotic or herbicide resistance markers. Seventy-one putative transformed hairy root lines from independent transformation events were established. Regeneration was induced in MS liquid medium supplemented with 30 microM 6-benzylaminopurine (BA), and the regenerants were multiplied on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Thus, the escape of the genes to wild relatives of these plants through pollen or other means is not possible or would be highly unlikely. In contrast, methods in other plant systems have been able to generate germline transformants from callus derived from tissues transformed through the hairy root method (Zdravković-Korać et al 2004;Crane et al 2006). Thus, the generation of germline transformed G. hirsutism directly from hairy roots is possible.…”
Section: Compatibility For Studies Involving Root-dwelling Organismsmentioning
confidence: 98%
“…Thus, the escape of the genes to wild relatives of these plants through pollen or other means is not possible or would be highly unlikely. In contrast, methods in other plant systems have been able to generate germline transformants from callus derived from tissues transformed through the hairy root method (Zdravković-Korać et al 2004;Crane et al 2006). Thus, the generation of germline transformed G. hirsutism directly from hairy roots is possible.…”
Section: Compatibility For Studies Involving Root-dwelling Organismsmentioning
confidence: 98%
“…The position effect influences the expression of the transgenes and consequently the growth and morphology of the hairy root clones. We found no correlation of escin content and the TL-DNA copy number, as clone 31, with the highest copy number of the TL-DNA (Zdravković-Korać et al, 2004) contained substantially lower amount of escin than clones 39 and 47 (Table 1). Thus, the differences in escin content among the hairy root clones are probably due to the TL-DNA position effect and the level of the transgene expression, which is in accordance with the results of Batra et al (2004) and Chaudhuri et al (2005).…”
Section: Resultsmentioning
confidence: 62%
“…The hairy root lines were obtained from independent transformation events and differ from each other in both the position of the TL-DNA insertion sites and the TL-DNA copy number, as was confirmed by Southern hybridization (Zdravković-Korać et al, 2004). The position effect influences the expression of the transgenes and consequently the growth and morphology of the hairy root clones.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that A. rhizogenes increases plant cellular sensitivity to auxin. This, in turn, enhances rooting percentage in many conifers and fruit trees (Holefors et al 1998;Damiano and Momticelli, 1998;VillalobosAmador et al 2002;Zdravkovic-Korac et al 2004). Furthermore, other research results indicate that the utilization of A. rhizogenes increases the root:shoot ratio (Casanova et al 2005), which may yield plantlets that are more tolerant to the stressful conditions in the field.…”
Section: Discussionmentioning
confidence: 91%